The place of familiar speech in the activity of a teacher - Likhachev Sergey Vladimirovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is devoted to the study of the means of familiar speech in the context of education. The teacher uses the means of familiar speech to achieve his speech goal of influencing the student. Familiarity either affects the addressee as expected or causes disagreement. The author of the article is looking for a solution to the question of the effective use of familiarity in the speech of a teacher.